Manajemen Pendidikan Pranikah dalam Membentuk Keluarga Sakinah pada Calon Pengantin - Sudirham Indra Jaya (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas (STIT PL) Gunung Tua, 2025)
This study examines the implementation of premarital education management in fostering harmonious families (keluarga sakinah) at the Religious Affairs Office (KUA) of Padangsidimpuan City, specifically in the North, South, and Southeast districts of Padangsidimpuan, conducted starting in September 2022. Marriage is a fundamental human need; besides being an act of worship to Allah, it also serves as a legitimate means of establishing proper and lawful relationships, thereby creating a harmonious family. This research employs a qualitative method with a normative descriptive approach to describe and analyze phenomena in the field. Data collection techniques include observation, interviews, and documentation, while data analysis is conducted through examination, marking, reconstruction, and systematization of data. To ensure data validity, techniques such as prolonged participation, diligent observation, triangulation, and member checking were used. The results indicate that the functions of premarital education management—including planning, organizing, implementation, and control—have been carried out effectively. This is expected to enhance participants’ understanding of creating a happy family characterized by sakinah (tranquility), mawaddah (love), and rahmah (compassion). Supporting factors for the program’s success include participants’ willingness to attend and actively participate, competent resource persons, and staff carrying out their duties responsibly. Conversely, inhibiting factors identified include delays or absences of some participants and insufficient funding or budget constraints. Overall, premarital education management at KUA Padangsidimpuan has played a crucial role in equipping prospective couples with the knowledge and understanding necessary to build harmonious families, although challenges remain that need improvement, particularly regarding participant engagement and budget availability.